An audit of phototherapy services at the department of dermatology in Inkosi Albert Luthuli Central Hospital: A 12-year cross-sectional study (2013-2024). - Shelembe, Lefalane Tshepisho; Mosam, Anisa; Chateau, Antoinette (Student’s Journal of Health Research Africa, 2025)
Background Phototherapy uses ultraviolet light to treat a range of dermatological diseases. An audit is necessary to provide a deeper understanding of the factors that may influence patient compliance with treatment. Methods A quantitative retrospectivetudy that included all dermatology patients who were treated with phototherapy at Inkosi Albert Luthuli Central Hospital during the study period. The data was obtained from the hospitalpaper records. The data was analysed for age, gender, race, diagnosis, and patient address. Patient records were also reviewed to determine reasons for stopping treatment. Results 167 patients were treated during the study period. 98 were females, and 69 were males. Most patients were African (51%), followed by those of Indian or Asian ethnicity (43%); White and Coloured patients comprised 2% each. The mean age was 48 years (SD 16.2, range 12-87). Overall, most patients treated had either vitiligo (38%) or psoriasis (34%). At the end of the study period, the proportion of patients still undergoing phototherapy was 24.55%, while those who had discontinued for various reasons were 75.45%. The reasons for stopping phototherapy included being lost to follow-up in 37%, financial constraints such as transport costs in 20%, treatment cessation due to improvement in 13%, side effects in 10%, work commitments in 10%, and lack of improvement or poor response to therapy in 10%. Forty-seven per cent of the patients lived within 20 kilometres of the hospital, 38% lived within 20-50 kilometres, and 16% resided at least 50 kilometres away. Conclusion Vitiligo and psoriasis are the most treated conditions with phototherapy at our centre. The distance of residence has no direct link to treatment cessation. Recommendations Further research is needed to determine the optimal treatment durations required for disease clearance and how this may impact adherence to phototherapy.